Teori Konstruktivisme dan Penerapannya dalam PAI Berbasis Inkuiri dan Proyek - Muhammad Fakhrul Islam Mh; Ahmad Zaini Al-Ma’rufi; Mamluatun Ni’mah (Qolamuna : Jurnal Studi Islam, 2026)
This article conceptually examines constructivist learning theory and its application in Islamic Religious Education (IRE) through inquiry based learning and Project Based Learning (PjBL). The scope of the study includes the theoretical foundations of constructivism, principles of constructivist learning, and the design of IRE instruction that integrates inquiry and project-based models to develop contextual religious understanding. The study aims to analyze the relevance of constructivist theory in IRE and to formulate a learning design that promotes student engagement, learner autonomy, and the internalization of Islamic values. This research employs a qualitative method using a conceptual-analytical library research approach. Data were collected from relevant academic sources, including books, national and international journal articles, and scholarly documents published within the last ten years. Data analysis was conducted using content analysis and descriptive-critical analysis. The findings indicate that constructivist theory positions students as active agents in constructing knowledge through experience, social interaction, and reflection. Inquiry based learning and PjBL are consistent with constructivist principles and effective in IRE instruction, particularly through a thematic tafsir approach. The integration of these approaches enhances deep religious understanding, critical thinking, and the practical application of Islamic values, making constructivist-based IRE a strategic response to contemporary educational challenges. Keywords : Constructivist Theory, Its Application, Islamic Religious Education, Inquiry-Based Learning,Project Based Learning (PjBL).italic)